Evaluation of merger premium and firm performance in Europe - Nnadi, Matthias; Aghanya, Daniel (World Academy of Science, Engineering and Technology, 2015)
This paper investigates whether the deal premium affects the performance of the acquiring firms in European mergers and acquisitions (M&As) deals for the period 2000-2013. We find a significant reduction in short-term performance of the acquiring firms after the M&As, reflecting the overpayment hypothesis. Our result also indicates that the negative effect on the performance of the acquiring firms is less pronounced in the long-term. The result confirms the synergy hypothesis and the existence of quadratic relationship between high premium and performance. Our findings are robust as we control for firm and time trends. The findings of our study have implications for companies engaging in acquisitions in Europe.
Keywords: mergers; premiums; performance; acquisition; Europe; returns